An optimized aggregate marker algorithm for bandwidth fairness improvement in classifying traffic networks - Al-Kharasani, Ameen Mohammed Abdulkarem; Othman, Mohamed; Abdullah, Azizol; Kweh, Yeah Lun (SpringerOpen, 2016)
The quality of service (QoS) requirements do not define a marker algorithm for service classes and managing network traffic to provide fair bandwidth sharing among aggregate flows. Additionally, the assured service is designed for applications relying on the Transmission Control Protocol (TCP). This article analyses and evaluates a new time sliding window traffic marker algorithm called the Optimized time sliding window Three Colour Marker (OtswTCM). The new design of the OtswTCM algorithm depends on the adaptability of the gamma (γ) concept in the Improved time sliding window Three Colour Marker (ItswTCM), the Double Improved time sliding window Three Colour Marker (I2tswTCM) and the Double Modified Double Improved time sliding window Three Colour Marker (M2I2tswTCM) algorithms to affect fairness and multiple protocols in classifying network traffic. This is achieved through separating marker TCP and User Datagram Protocol (UDP) and extending the marking probability for injecting more green and yellow traffic into the network. The marking probability mechanism was also studied to check how parameters in the traffic rate affect fairness. Extensive simulations were carried out to implement the algorithm using the NS2 simulator and compare the proposed marker algorithm with several other algorithms. The results show that the proposed marker algorithm is not affected by the number of flows and outperforms the previous marker algorithms in terms of fairness.